The Effect of Gadget on Mental Health Status and Social Interactions in Students at Public Junior High School 3 Pekuncen, Pekuncen Sub-District, Banyumas Regency - Panca Wahyu Safitri; Devita Elsanti (Proceedings Series on Health & Medical Sciences, 2022)
Background: Technology is growing rapidly in accordance with the times, especially gadgets that are designed to be complete and easy to carry, the type of gadget that is commonly used is usually a mobile phone. However, there are many negative impacts that arise in the use of gadgets for adolescents that can interfere with adolescent mental health and social interaction in adolescents. Social interaction is a relationship between individuals and groups that occurs because of social contact and communication. Objective: To analyze the effect of gadgets on mental health status and social interaction among students at public junior high school 3 Pekuncen. Methods: the research sample was 82 respondents who were taken using proportional random sampling technique. In study, three different types of questionnaires were used which were measured using an ordinal scale. Data processing in this study used the Chi-Square test. Results: Based on the results of the study, the p-values were 0,003 and 0,007. From these results it can be seen that the p-value is less than 0.05, which means that there is an effect of the gadget on mental healty status and the influence of the gadget on social interaction in students at public junior high school 3 Pekuncen. Conclusion: There is an effect of gadgets on mental health status and social interaction in students at public junior high school 3 Pekuncen.